Biophysics indicators as the sustainable strategy for river pollution control: Case study in Jangkok River, Mataram City, West Nusa Tenggara - Haryono, Iwan; Agustina, Haruki; Soesilo, Tri Edhi Budhi (Journal of Sustainability, Society, and Eco-Welfare, 2024)
Background: Sungai Jangkok is one of those considered heavily polluted in West Nusa Tenggara/Nusa Tenggara Barat (NTB), Indonesia. The Biochemical Oxygen Demand (BOD) value has exceeded the Class II water quality standard, and according to the Family Biotic Index (FBI) value, the river falls under the category of heavy organic pollution. The research objective is to realize sustainable management of the Jangkok Watershed by its river functions by implementing pollution control strategies. Methods: Data was collected using questionnaires and interviews with the public and stakeholders (government and NGOs). Water quality data was obtained from DLHK NTB and DLH Mataram City, and sampling was carried out using the composite sample technique. The methods employed were STORET, QUAL2Kw, logistic regression, and SWOT. Findings: The research findings indicate that, in general, the Jangkok River in Mataram City falls into the heavily polluted category from 2015 to 2022, with an average STORET score of -79.25. Moreover, the pollution loads of BOD, COD, and TSS entering the river have exceeded the pollution-carrying capacity. The condition is influenced by several factors, including the less favorable perception of pollution status (67%) and the usefulness of the river (59%) by the community. Additionally, the persistent behavior of littering and defecating in the river (23%), inadequate preventive practices (59%), insufficient wastewater disposal facilities (40%), and improper waste management (58%) are contributing factors. Moreover, houses backing up to the river (59%) also play a role in the current condition. Some causes are the need for more synergy across administrative regions between stakeholders, the absence of law enforcement for the community, dependency on the government budget for work programs, and the lack of incentives. Conclusion: The conclusion of this research suggests that the most effective strategy for taking is to develop a program for reducing pollutant loads that is integrated across districts and cities, integrated across agencies with various levels of authority, integrated with the community, and by the river's actual conditions and the socioeconomic community. Novelty/Originality of this Study: This study provides a novel approach by integrating quantitative water quality modeling (QUAL2Kw) with community behavior analysis to develop a sustainable and comprehensive strategy for controlling river pollution in the Jangkok watershed, Mataram City.